Ecology and Diversity of Small Indigenous Fishes in Four Fishing Sites of Upper Brahmaputra Basin, Assam, India - Nayak, Nipen; Majhi, Unmanaa; Bordoloi, Sharadindu; Basumatry, Dwimu; Baro, Daimalu; Doley, Biswadeep (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Small Indigenous fishes constitute important fishery resource of Assam, but doesn’t finds its place in capture fishery. Collection of these species is chiefly from their wild habitat and thus the study of these habitats become very important. The four sites selected for study namely Bogibeel, Madhupur, Maguri Beel and Sessa are well known fishing sites of Upper Assam known to record higher fish catch. These sites harbour variety of small indigenous fishes for both food and ornamental value. In our study we have recorded 41 different species of fishes of which 13 belonged to Family Cyprinidae. Channa bleheri and Ailia coila were the two Near Threatened (NT) fish found during the study. Systematic studies of the habitat directly or indirectly like studying the gut content of fishes will give significant information.